URGENSI AGAMA DALAM UPAYA PENANGGULANGAN KENAKALAN REMAJA - Hidayah, Rifa (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2005)
Expression of juvenile delinquency is often seen in society, for instance: attacking among students, free sex, and theft. The teaching of religious values and morality in teenager life comprehensively, becomes responsibility of family, society, school and government, as effort to solve the juvenile delinquency juvenile delinquency juvenile delinquency.The family requires applying the pattern of Islamic mothering. Society as a control conducts tight inspection to the teenager behavior and action. The school does not only emphasize on intellectual intelligence, it is also important to develop other intelligences, like emotional and spiritual intelligence. In consequence, religious subject is not merely given for memorizing (cognition), but also for being done affectively.Furthermore, the attitude of all elements of society must be good guidance. Parent, teacher, and society have not to disobey religious teaching, social norms and moral. It is the significant matter as effort to solve the juvenile delinquency.Keywords: religion and juvenile delinquency.